Patterns of Recurrence of Cutaneous Melanoma: A Literature Review - Dominga Peirano; Francisca Donoso; Sebastian Vargas; Leonel Hidalgo; Rosario Agüero; Pablo Uribe; Sebastian Mondaca; Cristian Patricio Navarrete-Dechent (Mattioli1885, 2023)
The incidence of melanoma has been dramatically increasing over the last decades. Melanoma is considered to have a high metastatic potential and it can progress due to hematogenous metastasis or via lymphatic vessels. Different patterns of recurrence have been described, namely, local, satellite, and in transit metastasis (LCIT), lymphatic, and systemic metastasis. With a more advanced melanoma stage at diagnosis, there is a higher risk for systemic metastasis in comparison to LCIT; in contrast, early-stage melanoma tends to recur more frequently as LCIT and less commonly as systematic metastasis. The aim of this review was to summarize the patterns of recurrence of cutaneous melanoma, giving the clinician a practical summary for diagnosis, prognosis, and surveillance. There is a knowledge gap of the common patterns of recurrence that needs to be addressed to better identify patients at high risk of disease recurrence and personalize surveillance strategies as well as patient counseling.